Features Of Helminth Infections In Clinical Pediatrics: Issues Of Diagnosis, Therapy, Prevention (Texas Journal of Medical Science, 2024)
The article shows the relevance of helminthiasis in pediatrics, the difficulties of diagnosis, modern approaches to therapy and prevention. The role of albendazole in the treatment of helminthiasis in children has been noted